A feasibility study on water resistant paper bag made from banana fibers and seaweed agar - Allapitan, Alexander B.; Barruga, Lorena J.; Corpuz, Janine Cathleen F.; Malimet, Ralph Victor M.
The ubiquity of using plastic bags over the years has resulted to various devastating effects for the environment. Plastic bags, along with other chemical-based packaging materials, are attributed as one of the many causes of deadly flooding in Metro Manila and the pollution of numerous water bodies all over the country. The government sets up the problems that inevitably come with the widespread use of plastic bags by failing to implement an effective and holistic solid waste management program. Subsequently, LGU's have started to introduce the idea of using paper bags as a means to replace plastic as checkout, take-away, and carry bags. While they incorporate the use of recycled materials, paper bags still necessitate a great amount of virgin pulp from wood to make the material durable. Hence, trees and forests are at stake with this proposition. The lack of a long-term solution to the problem creates a market opportunity for entrepreneurs to think of a new product to create and sell. This market opportunity influences the reason why the Eco-Banagar Bag is conceptualized, validated, and subjected to the feasibility study. The Eco-Banagar Bag's paper is made from 40% banana fibers, 40% recycled paper, and 20% other materials and is coated with a seaweed solution. It is initially targeted to cater to known environmentally-friendly businesses because it possesses an appropriate value proposition: a biodegradable packaging material that's also durable and water-resistant. The marketing of the product is centered on the tagline "RETHINK THE WAY WE PACK" as a means to establish the brand's surge as not only the different but also the best product in the market. The study forecasts the demand by assuming certain clients throughout the five years of the project study. These are the Rustan's Group of Companies, 7 Eleven, and Folded & Hung. The project requirements in setting up the business are identified in the technical phase. The plant is to be set up in a Philippine Economic Zone Authority location in Sta. Rosa, Laguna, where there are benefits for manufacturing firms, such as tax exemptions. The raw materials are sourced locally: banana fibers from Southern Tagalog, dry seaweeds from Region IV-B (Palawan, Mindoro), and scrap paper from Cavite. The machine requirements are determined from capacity planning and from the identification of the processes involved in making the product, which are preparation of raw materials, paper making, printing, lamination, reeling, and bag forming. The number of required machines is computed as follows: one Four drinier machine, two laminating machines, and nine paper bag forming machines for the first period of operations. These numbers double on the second year due to the increased demand obtained from having more clients. There are 10 machine operators needed for the first three years of operations, and an additional 10 more are to be added on the fourth year of operations. The labor costs are also composed of the direct and indirect employees hired by the company. As a final step to the technical phase, the identified costs are categorized and collated to provide an efficient reference for the financial study. Roughly PhP 25 million is needed to finance the initiation of the project. Fifty percent of this capital is obtained from equity financing and the other half is financed through the Land Bank of the Philippines' Easy Pondong Pang-asenso. In order to ensure ownership, the founders choose to buy 10 million shares (60%) at PhP 1.00 per share. The other 6.5 million shares are offered to investors. The financial statements reflect the cash flows, balance of the equity and assets, and the income of the business for 5 years. The ratios, furthermore, indicate profitability. The breakeven point is around 4.9 million units, which translates to around PhP 40.8 million. The social and economic costs and benefits are lastly evaluated to complete the social profitability phase of the project. The critical point to the implementation of the Eco-Banagar Bag is reliant on the product's social profitability, which is specifically centered on the environmental benefits it offers over the current packaging materials in the market. When the Eco-Banagar Bag gets manufactured, the product may start a domino effect among the whole packaging industry by steering it towards a greater use of human resources and technology in further developing and using natural materials to make biodegradable products. Several other benefits are also cited in the study, such as those obtained from recycling, income distribution, livelihood, support for the agricultural sector, taxes, and economic activity through NPV and IRR. In conclusion, the implementation of the Eco-Banagar Bag is deemed feasible, and if pushed through, may compel businesses to "RETHINK THE WAY WE PACK."